Performance evaluation of solar water heating system with heat pipe evacuated tubes provided with natural gas backup - Aamir Mehmood; Adeel Waqas; Zafar Said; Shek Mohammad Atiqure Rahman; Muhammad Akram (Energy Reports, 2019)
Present work is focused on building a TRNSYS simulation model of solar water heating (SWH) system using heat pipe evacuated tubes, hybridized with conventional fuel (i.e., natural gas) backup to provide uninterrupted thermal energy supply. An experimental facility was developed to validate the simulated model. Further, the performance of hybrid evacuated tube solar water heating (ETSWH) system was evaluated when it was thermally powered by a solar collector and conventional backup fuel. It was found that 23%-56% backup fuel could be saved by replacing conventional (gas) water heating system with the hybrid ETSWH system, which would additionally result in reduced greenhouse gas (GHG) emissions. The effects caused by concerned performance parameters, like water tubing insulation, differential temperature controller presence, and collector's plane area variations were also investigated. A comparison was conducted to reveal the performance of hybrid ETSWH system against a hybrid flat plate SWH (FPSWH) system. The findings show that hybrid ETSWH system is more efficient and eco-friendly with 1.87 benefit-cost ratio value and would result in annual natural gas savings of 8.79105 kWh that would lead to 175.539 U.S.-tCO2 emissions reduction, whereas hybrid FPSWH system with 1.64 benefit-cost ratio value would result in 6.45105 kWh annual natural gas fuel savings.
Keywords: 330; Evacuated tube collector; Flat plate collector; Gas water heater; Performance parameters; Solar thermal energy; TRNSYS